Program TPQ Lansia: Upaya Meningkatkan Kemampuan Membaca Al-Qur’an di Kalangan Lanjut Usia: TPQ Elderly Program: Efforts to Improve the Ability to Read the Al-Qur'an among the Elderly - Miftachuddin, Miftachuddin; Saifudin, Ahmad; Fitriani, Yeni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Many elderly people in Carikan Hamlet cannot yet read the Koran, and there are no special learning programs for them. Therefore, TPQ Elderly was established to provide Al-Qur'an learning that suits the needs of the elderly. The TPQ Elderly Program was introduced to the community through pamphlets and direct outreach through religious activities and village events. Learning begins with the introduction of hijaiyah letters using teaching aids and continues with methods suitable for the elderly. Even though there are obstacles such as limited time because activities can be carried out after Maghrib prayers, efforts have been made to create a pleasant and comfortable atmosphere and adapt learning methods to help the understanding of TPQ Elderly participants. Continuous evaluation will be carried out to assess the extent of effectiveness in helping elderly people read the Koran properly and correctly. Thus, through the PAR approach and implementation of the TPQ for the Elderly, the hope is to improve the ability to read the Koran in Carikan Hamlet and allow them to engage in meaningful religious activities in their old age.